2018
DOI: 10.1111/phen.12272
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of novel β‐1,3‐glucan recognition proteins from a Tibetan Plateau ghost moth Thitarodes pui (Lepidoptera, Hepialidae)

Abstract: β‐1,3‐glucan recognition proteins (βGRPs) function as pattern recognition receptors in the innate immune response against invading pathogens. In the present study, we obtain full‐length cDNA clones for two novel putative βGRPs: TpβGRPc and TpβGRPd from the ghost moth Thitarodes pui (Lepidoptera: Hepialidae). Phylogenetic analysis shows a small distinct lineage, βGRP clade 4, consisting of T. pui βGRPs including TpβGRPa and TpβGRPb that have been identified previously. TpβGRPc and TpβGRPd, comprising 488 and 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…In the current study, the expression levels of GmBGRP gene were the highest in the pupal stage, and the lowest in the adult stage. This is consistent with the report that TpβGRPa and TpβGRPb may be required for pupal development in Thitarodes pui (Sun et al, 2019). However, the developmental expression level of BGRP has been investigated in other insects, but the results were inconsistent with this study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current study, the expression levels of GmBGRP gene were the highest in the pupal stage, and the lowest in the adult stage. This is consistent with the report that TpβGRPa and TpβGRPb may be required for pupal development in Thitarodes pui (Sun et al, 2019). However, the developmental expression level of BGRP has been investigated in other insects, but the results were inconsistent with this study.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the expression level of GmBGRP is also different at different times after infection. Previous studies reported that, in T. pui , TpβGRPc transcript significantly decreased at 1 h and then increased approximately twofold at 3 h after fungal infection (Sun et al, 2019). These results indicate that GmBGRP plays an important role in the immune response to fungal infections, but the specific mechanism in G. molesta needs to be further studied.…”
Section: Discussionmentioning
confidence: 90%
“…This polysaccharide is detected by β-1,3-glucan recognition proteins (βGRPs/GNBPs) [ 60 , 61 ]. Receptors of this type have been identified, e.g., in B. mori, D. melanogaster, G. mellonella, Manduca sexta, Plodia interpuncella, Tenebrio molitor , and Thitarodes pui [ 44 , 62 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%